Readiness Level of Employees in Position Transfers at State Universities: Analysis of State Administrative Law Perspective - Siti Mursidah; Eko Handoyo; Mulyo Widodo (Universitas Negeri Semarang (UNNES), 2022)
The post-holder now has to adapt the new simplified regulation about changing structural position from echelon III and IV to the functional position. Since this regulation has been issued recently, they sometimes will experience the feeling of pessimism, anxiety or worry in playing the role of the new position. The problems to be solved in this research are: 1) what are the problems faced by the functional post-holder? 2) what is the strategy adopted in carrying out the duties and functions of functional post-holder? This study uses a qualitative and quantitative approach with a mix-method. This study take place in the representatives of state universities in Indonesia. The mix-method was used to obtain comprehensive results on the readiness of education personnel whose function was switched from structural positions to functional position in universities under the Ministry of Education, Cultural, Research and Technology who were affected by the changing of echelon III and IV structural positions. The conclusion of this study is that education personnel whose function was switched from structural positions to functional position experience problems including incompatibility of educational background with their functional position, incompatibility of job desk with their interests and expectations. The incompatibility of functional position with the placement of job unit causes lack of positive impact on their working record and the decrease of financial support.